Conservation of deltaic mangrove forest resources in Kuching, Sarawak: local communities' willingness to pay - Shuib, Ahmad; Bon, Anna Sin Yii; Edman, Salbiah (Forestry Department Peninsular Malaysia, 2012)
The mangrove forest resources in the Kuching Delta are being exploited extensively for agricultural, industrial and other development purposes despite conservation efforts being carried out. This study was aimed at determining the willingness to pay by the local communities for the conservation of the mangrove resources. Data were collected from the local communities living near the mangrove forests and the WTP was obtained by using the contingency valuation technique. 316 respondents were interviewed and asked to indicate the maximum amount they were willing to pay for the conservation of mangrove forest resources. The majority of the local community members were willing to pay for the conservation of the resources, with a mean value of RM15.70 per year per person. Conservation of the resources was perceived positively by the residents with a mean value of 3.9 (out of 5 rating scale). Levels of education and income of the local communities have positive influence on the willingness to pay for conservation of the resources. Mangrove forest benefits could be obtained in perpetuity if conserved; the estimated gross present value of the benefits (WTP) is RM28.3 million, at the annual social discount rate of 4 %.